Afiksasi Verba Triliteral Dalam "Hadits Innallaha Thoyyibun Laa Yaqbalu Illa Thoyyiban" (Analisis Morfologi) (Al-Hasani: Journal of Islamic Studies, 2024)
Affixation is the process of changing the form of a root word by adding letters (affixes), which in Arabic is termed Ahruf Al Ziyadah, leading to changes in form and meaning. For example, affixation in triliteral verbs, which are commonly found in Arabic texts, particularly in hadith such as "Innallaha Thoyyibun Laa Yaqbalu Illa Thoyyiban." The triliteral verb in this hadith should be analyzed morphologically (in the science of Sarf), so it can be utilized in teaching morphology to Arabic language students in Indonesia, as this hadith is widely memorized and easily accessible. This research aims to describe and analyze the triliteral verbs in the hadith "Innallaha Thoyyibun Laa Yaqbalu Illa Thoyyiban" through morphological analysis according to the perspectives of morphology experts like Ibn Ushfur, Ibn Malik, and Gorys Keraf. This writing is a qualitative descriptive study. It uses the library research method, where the author reads books, magazines, journals, and sources related to the object of writing. After analyzing the data, it was found that affixation of triliteral verbs, according to the perspectives of Ibn Ushfur, Ibn Malik, and Gorys Keraf in the hadith "Innallaha Thoyyibun Laa Yaqbalu Illa Thoyyiban," involves eight (8) triliteral mujarad verbs that undergo affixation processes including prefixes, suffixes, or confixes. Additionally, there are four (4) triliteral mazid verbs that undergo affixation processes involving prefixes, suffixes, or confixes.